TRPV4, TRPC1, and TRPP2 assemble to form a flow‐sensitive heteromeric channel. Issue 11 (11th August 2014) - Du, Juan; Ma, Xin; Shen, Bing; Huang, Yu; Birnbaumer, Lutz; Yao, Xiaoqiang
Abstract : Transient receptor potential (TRP) channels, a superfamily of ion channels, can be divided into 7 subfamilies, including TRPV, TRPC, TRPP, and 4 others. Functional TRP channels are tetrameric complexes consisting of 4 pore‐forming subunits. The purpose of this study was to explore the heteromerization of TRP subunits crossing different TRP subfamilies. Two‐step coimmunoprecipitation (co‐IP) and fluorescence resonance energy transfer (FRET) were used to determine the interaction of the different TRP subunits. Patch‐clamp and cytosolic Ca 2+ measurements were used to determine the functional role of the ion channels in flow conditions. The analysis demonstrated the formation of a heteromeric TRPV4‐C1‐P2 complex in primary cultured rat mesenteric artery endothelial cells (MAECs) and HEK293 cells that were cotransfected with TRPV4, TRPC1, and TRPP2. In functional experiments, pore‐dead mutants for each of these 3 TRP isoforms nearly abolished the flow‐induced cation currents and Ca 2+ increase, suggesting that all 3 TRPs contribute to the ion permeation pore of the channels. We identified the first heteromeric TRP channels composed of subunits from 3 different TRP subfamilies. Functionally, this heteromeric TRPV4‐C1‐P2 channel mediates the flow‐induced Ca 2+ increase in native vascular endothelial cells.—Du, J., Ma, X., Shen, B., Huang, Y., Birnbaumer, L., Yao, X., TRPV4, TRPC1, and TRPP2 assemble to form a flow‐sensitive heteromeric channel. FASEB J. 28, 4677–4685 (2014). www.fasebj.org